BLOOD-CONSTITUENTS AND ELECTROPHORETIC PATTERNS IN ANTARCTIC BIRDS - PENGUINS AND SKUAS - Rosa, C. D.; Rosa, R.; Rodrigues, E.; Bacila, M. (Elsevier B.V., 1993)
1. A survey has been carried out on the blood constituents of penguins from the Pygoscellidae family, Pygoscellis antartica, P. papua and P. adeliae, and of skuas (Chataracta maccormicki).2. Glucose, non-protein nitrogen compounds, proteins, lipids and inorganic compounds and the electrophoretic patterns for hemoglobin, serum proteins and lipoproteins were studied.3. The values obtained for glucose partition in the blood, glycosylated hemoglobin and non-protein nitrogen compounds, are discussed.